Hygienic-sanitary quality of peanuts commercialized in Campinas, São Paulo, Brazil, and the toxigenic potential of fungi isolated from peanuts: - Scomparin Ribeiro, Ana Beatriz Scomparin; Arias, Luna Valentina Angulo; Bonsaglia, Erika Carolina Romão; Morasi, Rafaela Martins; Silva, Nathália Cristina Cirone; Pereira, Erik da Silva; Soto, Taynara Souza; Rocha, Liliana de Oliveira (Food Science and Technology, 2025)
Food safety is a topic of high relevance, with Salmonella and Escherichia coli being pathogenic microorganisms associated with foodborne outbreaks worldwide, and Aspergillus flavus is a contaminant able to produce aflatoxins, a highly toxic mycotoxin that may be present in various commodities. Food contamination can occur at various stages along the production and processing pathways. Peanuts, despite being low-cost products with numerous nutritional advantages, are susceptible to microbiological contamination by foodborne bacteria and aflatoxins. Thus, to assess the food safety of commercially available peanuts in Campinas, two sample groups were collected and analyzed: bulk peanuts and packaged peanuts. The analysis involved the presence or absence of Salmonella, enumerating the populations of E. coli, Enterobacteria, yeast, and molds, particularly Aspergillus spp., and evaluating the toxigenic potential of the isolated strains. Among the main findings, it was observed that the samples were not contaminated with Salmonella or E. coli; however, Enterobacteria, yeast, and molds and toxicogenic potential were detected, particularly in bulk peanut samples. This demonstrates the importance of washing or treating fresh foods before consumption and highlights the need for companies handling these products to implement more rigorous quality control and monitoring measures to ensure the safety of the commercialized products.